Incentive strategy for energy efficiency programs in industries consuming 6000 TOE/year with sustainable energy performance - Martoyoedo, Satryo; Priyadi, Priyadi; Fajrie, Dewanto; Ariati, Ratna; Yandri, Erkata; Hendroko Setyobudi, Roy; Suherman, Suherman; Burlakovs, Juris; Mel, Maizirwan; Krido Wahono, Satriyo; Heri Purnomo, Agus; Fauzi, Ahmad; et al. (EDP Sciences, 2023)
This study aims to obtain the incentives strategy that can increase the participation of energy users greater than or equal to 6000-TOE in fulfilling their obligations on energy conservation through energy management with Sustainable Energy Performance (SEP). Several steps need to be carried out. First, data collection on industries that must carry out energy management, and will be analyzed to determine the level of compliance of energy users. Second, ensure that already have carried out an energysaving program with the SEP. Third, formulating incentive schemes for energy users. Fourth, the interest deduction for the company when they implement the SEP. The results show that only 10.25 % fully comply with the regulation, 36.89 % are partially compliant and 52.87 % are not compliant with energy management activities at all. For industries that have implemented energy conservation and SEP, several benefits are obtained, including capital expenditure (capex) savings when purchasing new imported equipment for creating another energy efficiency, by up to 30 % and incentives in the form of lowering interest rates by up to 4 %.